OCCURRENCE OF HETEROCARPUS SIBOGAE DE MAN AND PLESIONIKA WILLIAMSI FOREST (CRUSTACEA, DECAPOD A, PANDALIDAE) IN THE ARABIAN SEA - Suseelan, C (Indian Journal of Fisheries, 2011)
The occurrence of two species of deep-sea prawns, namely Heterocarpus sibogae De Man and PlesionikawUliamsi Forest in the Arabian Sea is reported for the first time. The material is described and illustrated